2019
DOI: 10.2147/ott.s193031
|View full text |Cite
|
Sign up to set email alerts
|

<p>circZNF609 promotes the proliferation and migration of gastric cancer by sponging miR-483-3p and regulating CDK6</p>

Abstract: ObjectiveTo explore the regulatory effects of circZNF609 on proliferative and migratory capacities of gastric cancer (GC) and its underlying mechanism.MethodsExpression level of circZNF609, CDK6 and miR-483-3p in GC tissues and cells were detected qRT-PCR verification. CCK-8 and transwell assay were conducted the cell viability and migratory capacities of GC cells. Dual luciferase assay was enrolled to confirm the interaction among circZNF609, CDK6 and miR-483-3p. Western blot was used to detect the protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…22 CircZNF609 enhanced gastric cancer migration and invasion through modulating CDK6 via sponging miR-483-3p. 23 In this study, we predicted miRNA targets of circZNF609 by CircBank informatic tool. Among the potential targets, we chose miR-342-3p for further study due to its anti-tumor features reported previously.…”
Section: Dovepressmentioning
confidence: 99%
“…22 CircZNF609 enhanced gastric cancer migration and invasion through modulating CDK6 via sponging miR-483-3p. 23 In this study, we predicted miRNA targets of circZNF609 by CircBank informatic tool. Among the potential targets, we chose miR-342-3p for further study due to its anti-tumor features reported previously.…”
Section: Dovepressmentioning
confidence: 99%
“…Because circZNF609 has been reported to work as a competing endogenous RNA for many miRNAs ( He et al., 2020 ; Jin et al., 2019 ; Zhu et al., 2019 ; Liu et al., 2021 ; Wang et al., 2018 ; Wu et al., 2019 ; Liu et al., 2019 ), we checked whether the modulation of CKAP5 mRNA by circZNF609 could be mediated by some miRNAs targeting both transcripts. We found no significant shared binding sites of microRNAs expressed in RD cells among circZNF609 and CKAP5 mRNA ( Figure S4 C), ruling out an miRNA-mediated effect.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we studied circRNA zinc finger protein 609 (circZNF609), a circRNA previously described to be regulated and to control human primary myoblast and embryonal rhabdomyosarcoma (ERMS) cell proliferation ( Legnini et al., 2017 ; Rossi et al., 2019 ; di Timoteo et al., 2020 ). CircZNF609 was found to also be upregulated in several types of human cancers, such as prostate cancer ( Jin et al., 2019 ), breast cancer ( Wang et al., 2018 ), gastric cancer ( Wu et al., 2019 ; Liu et al., 2019 ), nasopharyngeal carcinoma ( Zhu et al., 2019 ; Liu et al., 2021 ), and hepatocellular carcinoma ( He et al., 2020 ), where its depletion has been linked with reduced aggressiveness of tumor cells. Although those studies pointed to circZNF609 as an miRNA sponge, we significantly advanced our understanding of the molecular mechanism through which it affects cell proliferation by focusing on its interactions with mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Forty‐three articles including non‐data studies, non‐prognosis studies, nonhuman studies, and noncompliant studies were excluded through intensive reading of the full text. Finally, 35 literature studies with a total of 3135 patients were included in this meta‐analysis 8,10,12–44 . The process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%